2014
DOI: 10.7860/jcdr/2014/7901.4533
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lipid Profile and Uric Acid with Pre-Eclampsia of Third Trimester in Nullipara Women

Abstract: Background: Pre-eclampsia (PE) affects approximately 3% of all pregnancies worldwide, with onset of symptoms in the late second or third trimester, commonly after 32 nd week. It is common in nulliparous women. To avoid complications it is necessary to diagnose it in advance, but the available tools are unable to clinch the diagnosis of preeclampsia effectively in majority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
4
6
0
Order By: Relevance
“…However, in preeclampsia, there is dysregulation of lipid metabolism, which manifests as abnormal maternal serum lipid levels [32][33][34]. Consistent with this study, several other studies have reported dyslipidaemia in preeclampsia and stated that abnormal lipid levels in pregnancy signi cantly contribute to the development of preeclampsia through the excessive deposition of triglycerides in the uterine spiral arteries which may result in endothelial dysfunction through the production of small dense LDL [32][33][34][35][36]. Although the women with preeclampsia in this study presented with abnormal serum lipid, no signi cant association between vitamin D de ciency and lipid was observed in both the normotensive women and preeclamptic women after adjusting for possible confounders.…”
Section: Discussionsupporting
confidence: 78%
“…However, in preeclampsia, there is dysregulation of lipid metabolism, which manifests as abnormal maternal serum lipid levels [32][33][34]. Consistent with this study, several other studies have reported dyslipidaemia in preeclampsia and stated that abnormal lipid levels in pregnancy signi cantly contribute to the development of preeclampsia through the excessive deposition of triglycerides in the uterine spiral arteries which may result in endothelial dysfunction through the production of small dense LDL [32][33][34][35][36]. Although the women with preeclampsia in this study presented with abnormal serum lipid, no signi cant association between vitamin D de ciency and lipid was observed in both the normotensive women and preeclamptic women after adjusting for possible confounders.…”
Section: Discussionsupporting
confidence: 78%
“…*P < .05, significant; **P < .01, very significant, compared with the control group severity of HDCP and assist in further studying the cause and pathophysiology of HDCP. Our findings are consistent with previous studies,15,[17][18][19] which implicated metabolic and inflammatory changes involved in the pathogenesis of preeclampsia. However, previous studies mostly recruited patients with MPE or SPE.…”
supporting
confidence: 94%
“…Differential expressed lipid profile and cytokines were found to gradually increase or decrease according to the severity of HDCP, which suggests that lipid profile and cytokines could predict the severity of HDCP and assist in further studying the cause and pathophysiology of HDCP. Our findings are consistent with previous studies, which implicated metabolic and inflammatory changes involved in the pathogenesis of preeclampsia. However, previous studies mostly recruited patients with MPE or SPE.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have tried to elucidate the association between the maternal serum lipid profiles and pre-eclampsia, but many of them have reported conflicting results. Some studies have shown higher levels of lipid profiles in pre-eclamptic women as compared to normotensive pregnant women [ 9 , 11 13 ]. However, a few studies have found non-significant difference in the serum levels of maternal lipid profiles between pre-eclamptic and normotensive pregnant women [ 14 , 15 ] and few other reports indicated lower serum lipid profiles in pre-eclamptic women as compared to normotensive controls.…”
Section: Introductionmentioning
confidence: 99%